2022
DOI: 10.3390/brainsci12081087
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Repetition Motor Imagery Training and Physical Practice Training Exert the Growth of Fatigue and Its Effect on Performance

Abstract: Continuous repetition of motor imagery leads to mental fatigue. This study aimed to examine whether fatigue caused by motor imagery training affects improvement in performance and the change in corticospinal excitability. The participants were divided into “physical practice training” and “motor imagery training” groups, and a visuomotor task (set at 50% of maximal voluntary contraction in participants) was performed to assess the training effect on fatigue. The measurements were recorded before and after trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…An original finding of the present study is that the amount of effort required to complete imagined actions is mirrored by mental fatigue. This confirms the embodied nature of MI and corroborates past observations of comparable mental fatigue profiles after physical practice or MI training [15]. From a practical standpoint, this suggests that dose-response relationships guidelines for MI intervention in sports and rehabilitation should account for the demands of the tasks targeted by the MI intervention.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…An original finding of the present study is that the amount of effort required to complete imagined actions is mirrored by mental fatigue. This confirms the embodied nature of MI and corroborates past observations of comparable mental fatigue profiles after physical practice or MI training [15]. From a practical standpoint, this suggests that dose-response relationships guidelines for MI intervention in sports and rehabilitation should account for the demands of the tasks targeted by the MI intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, mental fatigue induced by MI practice appeared to have negative effects on endurance paradigms involving submaximal contractions or speed-accuracy tradeoffs [14][15][16]. By contrast, maximal isometric force performance was shown unaffected [12].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As the primary structure that generate the motor commands to the muscles for various physical tasks, changes in the excitability of the primary motor cortex (M1) may underlie the impaired motor performance that developed due to mental fatigue (28,29). Over the years, several studies have investigated the changes in the excitability of the M1 following prolonged or sustained cognitive exertion leading to mental fatigue (28,(30)(31)(32)(33). However, the findings of these studies are inconsistent with some studies showing an increase in corticospinal excitability (32), while others found a decrease (33) or no change (28,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several studies have investigated the changes in the excitability of the M1 following prolonged or sustained cognitive exertion leading to mental fatigue (28,(30)(31)(32)(33). However, the findings of these studies are inconsistent with some studies showing an increase in corticospinal excitability (32), while others found a decrease (33) or no change (28,30,31). In addition to methodological differences, all the studies have primarily focused on changes in transcranial magnetic stimulation (TMS) evoked motor evoked potentials (MEPs) peak-to-peak amplitude which is an index of corticospinal excitability (CSE).…”
Section: Introductionmentioning
confidence: 99%